2015
DOI: 10.1097/mpa.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinical Presentations of Hyperlipidemic Acute Pancreatitis

Abstract: Different clinical presentations of HLAP should be applied to be distinguished from non-HLAP in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 12 publications
5
41
1
3
Order By: Relevance
“…In the present study, patients with HTGAP accounted for 12.2% (40/329) of all patients with AP. We found that younger age, diabetes mellitus, fatty liver, a high recurrence rate and a more severe prognosis were more commonly observed in HTGAP, a finding similar to that reported in recent studies …”
Section: Discussionsupporting
confidence: 92%
“…In the present study, patients with HTGAP accounted for 12.2% (40/329) of all patients with AP. We found that younger age, diabetes mellitus, fatty liver, a high recurrence rate and a more severe prognosis were more commonly observed in HTGAP, a finding similar to that reported in recent studies …”
Section: Discussionsupporting
confidence: 92%
“…Hypertriglyceridemiainduced acute pancreatitis (HTG-AP) is defined by serum triglyceride (TG) level exceeding 11.3 mmol/L (1000 mg/ dL) or between 5.6 to 11.3 mmol/L (500~1000 mg/dL) together with lipemic serum [5,6]. As compared to other etiologies, HTG-AP is usually more severe and has higher recurrence rate [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that the most common etiologies of AP are gallstone disease and alcohol abuse. Currently, 12%-20% of patients with AP have previous hypertriglyceridemia, which has become a well-recognized etiology[ 2 - 4 ]. Hyperlipidemic acute pancreatitis (HLAP) is a form of AP occurring in the presence of severe hypertriglyceridemia and in the absence of other causes[ 5 ].…”
Section: Introductionmentioning
confidence: 99%